2013
DOI: 10.1080/02755947.2012.760504
|View full text |Cite
|
Sign up to set email alerts
|

Spawning Substrate Size, Shape, and Siltation Influence Walleye Egg Retention

Abstract: We compared Walleye Sander vitreus egg retention among varying rock treatments placed in a hydraulic flume to test the influence of spawning substrate shape and size on egg retention and the influence of substrate siltation on egg adhesiveness. Egg loss from suboptimal spawning substrates has been hypothesized as a substantial source of mortality during the incubation period. To investigate the influence of substrate size and shape on Walleye egg retention, known numbers of Walleye eggs were pipetted onto rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…For example, the Maumee and Sandusky rivers flow through watersheds dominated by agricultural land use with low gradients and are subsequently highly responsive to regional temperature fluctuations and extreme precipitation events (Richards 1990;Pritt et al, unpublished manuscript). High variability in temperature and flow regimes in these systems can influence timing of production and larval survival (Mion et al 1998, Crane and Farrell 2013, Pritt et al 2013. The open-lake reef complex is located in relatively shallow water influenced by Maumee and Detroit River discharge, and is responsive to regional temperature fluctuations.…”
Section: System Descriptionmentioning
confidence: 99%
“…For example, the Maumee and Sandusky rivers flow through watersheds dominated by agricultural land use with low gradients and are subsequently highly responsive to regional temperature fluctuations and extreme precipitation events (Richards 1990;Pritt et al, unpublished manuscript). High variability in temperature and flow regimes in these systems can influence timing of production and larval survival (Mion et al 1998, Crane and Farrell 2013, Pritt et al 2013. The open-lake reef complex is located in relatively shallow water influenced by Maumee and Detroit River discharge, and is responsive to regional temperature fluctuations.…”
Section: System Descriptionmentioning
confidence: 99%
“…It is likely that after losing their adhesiveness, eggs that settle into interstitial spaces in coarse substrates are additionally protected from wave transport owing to substrate roughness (Bozek et al 2011b). Crane and Farrell (2013) found a mean retention of nonadhesive walleye eggs of 57.5% at 95 cm·s −1 up to 59.8% at 55 cm·s −1 in various gravel mixtures and that coarse gravel (16-45 mm) retained walleye eggs at a higher rate than even very coarse gravel (23-90 mm), suggesting an optimal substrate size for egg retainment and survival. In addition, gravel matrices are more stable than sand because of higher C v values and multiple layers often mixed with other coarse substrates.…”
Section: Period Onementioning
confidence: 89%
“…laboratory flume study, Crane and Farrell (2013) found clean coarse substrates could retain adhesive eggs at 65 cm·s −1 but that "silt-covered coarse substrates" could not. It is likely that after losing their adhesiveness, eggs that settle into interstitial spaces in coarse substrates are additionally protected from wave transport owing to substrate roughness (Bozek et al 2011b).…”
Section: Period Onementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, walleye eggs were never collected at the coal cinder pile in North Channel Saint Clair River-a presumably preferable substrate compared to sand and clay. It was noted that the creation of reefs in both rivers has shown no obvious impact on where walleye, lake whitefish, and suckers choose to spawn but has likely increased the survival of eggs deposited over them by decreasing rates of egg siltation, predation, or of being washed downstream (Crane and Farrell, 2013).…”
Section: Discussionmentioning
confidence: 99%